KECERDASAN EMOSIONAL DAN PENCAPAIAN PRESTASI AKADEMIK MAHASISWA DI JURUSAN AKUNTANSI POLITEKNIK NEGERI SRIWIJAYA - Maria . (Universitas PGRI Palembang, 2012)
This research aims to measure the effect of Emotional Quotient (EQ) toward the attainment of academic achievement at accounting department Polsri both simultaneously and partially. Its contribution would have been expected to ideas towards the importance of emotional intelligence in the world of student academic achievement and preparation to enter the workforce later. In addition, the expediency of emotional intelligence will contribute to the learning process of accounting that has a comprehensive strategy encompassing skills/expertise, knowledge, and professional orientation. The data has been gathered by sampling to student at accounting department Polsri. The research samples are 344 respondents selected by stratified random. This type of research is descriptive-verifikatif. The result indicated that self awareness, self regulation, motivation, empathy and social skill have influences toward the attainment of academic achievement both simultaneously and partially. Entirely, the result identified about the self awareness, self regulation, motivation, empathy and social skill have significantly effects to academic achievement at accounting department Polsri Key words: emotional quotient, academic achievement